2010
DOI: 10.1007/s11664-010-1336-8
|View full text |Cite
|
Sign up to set email alerts
|

Interfacial Reactions of Sn-58Bi and Sn-9Zn Lead-Free Solders with Au/Ni/SUS304 Multilayer Substrate

Abstract: The liquid/solid interfacial reactions of Sn-58Bi (SB) and Sn-9Zn (SZ) lead-free solders with Au/Ni/SUS304 multilayer substrates have been investigated in this study. In the SB/Au/Ni/SUS304 couple, only the Ni 3 Sn 4 phase with needle-like grains was formed at the SB/Au/Ni/SUS304 interface. The Ni 5 Zn 21 phase with a column structure was formed at the SZ/Au/Ni/SUS304 interface. The thickness of both intermetallic compounds (IMCs) increased with increasing reaction temperature and time. Meanwhile, the growth m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
1

Year Published

2011
2011
2017
2017

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 28 publications
(15 reference statements)
0
7
1
Order By: Relevance
“…The prefactor and apparent activation energy were determined to be 7.3 Â 10 À3 m s À1 and 8.4 Â 10 À11 m 2 s À1 , and 70.4 kJ/mol and 47.2 kJ/mol for chemical reaction and diffusion, respectively. Compared the previous studies [10,14], the activation energy for diffusion presented in this work was relatively smaller. Chan et al [10] reported the activation energy to be 68.9 kJ/mol.…”
Section: Liquid/solid Snezn/ni Interfacial Reactionscontrasting
confidence: 63%
See 2 more Smart Citations
“…The prefactor and apparent activation energy were determined to be 7.3 Â 10 À3 m s À1 and 8.4 Â 10 À11 m 2 s À1 , and 70.4 kJ/mol and 47.2 kJ/mol for chemical reaction and diffusion, respectively. Compared the previous studies [10,14], the activation energy for diffusion presented in this work was relatively smaller. Chan et al [10] reported the activation energy to be 68.9 kJ/mol.…”
Section: Liquid/solid Snezn/ni Interfacial Reactionscontrasting
confidence: 63%
“…Chan et al [10] reported the activation energy to be 68.9 kJ/mol. Recently, Yen and his coworkers [14] studied the interfacial reactions of Sn-9wt%Zn solders with Au/Ni/SUS304 substrate and they determined the activation energy for Ni 5 Zn 21 growth to be 92.6 kJ/mol. In addition, the corresponding results were summarized in Table 4(a) and (b).…”
Section: Liquid/solid Snezn/ni Interfacial Reactionsmentioning
confidence: 99%
See 1 more Smart Citation
“…An Au/Pd/Ni multilayer structure is commonly electroplated onto a metallic substrate surface to improve the joint reliability and wettability between the solder and substrate. Numerous studies have reported on the interfacial reactions of Pb-free solders with Au/Pd/Ni/metallic substrates [14][15][16][17][18][19][20][21][22][23][24][25][26]. However, research on the interfacial reactions between the solder and Au/Pd/Ni/brass systems is lacking.…”
Section: Introductionmentioning
confidence: 99%
“…10,19,20 In our previous study, 10 the effects of Zn content (1 wt.% to 9 wt.%) in Sn-Zn solders were investigated at the Ni interface. As the Zn content is decreased below 2 wt.% Zn, the dominant phase changes from Ni 5 Zn 21 to (Ni,Zn) 3 Sn 4 .…”
Section: Introductionmentioning
confidence: 99%